The match between motivation and performance management of health sector workers in Mali - Touré Hamadassalia; Toonen Jurrien; Dieleman Marjolein; Martineau Tim (BMC, 2006)
Abstract Human resources for health (HRH) play a central role in improving accessibility to services and quality of care. Their motivation influences this. In Mali, operational research was conducted to identify the match between motivation and the range and use of performance management activities. Objectives To describe the factors motivating and demotivating health workers in Mali and match the motivators with the implementation of performance management. Methods First an exploratory qualitative study was conducted: 28 interviews and eight group discussions were held. This was followed by a cross-sectional survey, during which 370 health workers were interviewed. The study population consisted of health workers of eight professional groups. The following issues were investigated: • motivating and demotivating factors; • experiences with performance management, including: job descriptions, continuous education, supervision, performance appraisal and career development. Findings The study showed that the main motivators of health workers were related to responsibility, training and recognition, next to salary. These can be influenced by performance management (job descriptions, supervisions, continuous education and performance appraisal). Performance management is not optimally implemented in Mali, as job descriptions were not present or were inappropriate; only 13% of interviewees received 4× per year supervision, and training needs were not analysed. Some 48% of the interviewees knew their performance had been appraised in the last two years; the appraisals were perceived as subjective. No other methods were in place to show recognition. The results enabled the research team to propose adaptations or improvements upon existing performance management. Conclusion The results showed the importance of adapting or improving upon performance management strategies to influence staff motivation. This can be done by matching performance management activities to motivators identified by operational research.